Extrinsically microporous polymer membranes derived from thermally cross-linked perfluorinated aryl-ether-free polymers for gas separation - Shin, Ju Ho; Yu, Hyun Jung; Jung, Jiyoon; An, Heseong; Park, Jung Hoon; Lee, Albert S.; Lee, Jong Suk (Nature Publishing Group, 2025)
State-of-the-art membranes derived from polymers of intrinsic microporosity offer promising alternatives to energy-intensive, thermally driven separation techniques but often suffer from reduced performance under condensable gases or physical aging. Here, extrinsically microporous polymer membranes (EMPMs) are introduced as a distinct class of microporous membranes, fabricated from perfluorinated aryl-ether-free aromatic polymers via defluorination-induced thermal cross-linking. This process generates extrinsic micropores, increases intersegmental distances, and significantly enhances gas permeability. EMPMs exhibit a Brunauer-Emmett-Teller surface area of 552 m2 g-1 and demonstrate exceptional plasticization resistance under equimolar CO2/CH4 mixed gas at pressures up to 40 bar. CO2 permeability increases from 280 to 12,000 Barrer at 1 bar and 35 degrees C, while CO2/N2 selectivity reaches 46 at -20 degrees C, surpassing the 2019 polymeric upper bound. Furthermore, extrinsically microporous hollow fiber membranes prepared via dip-coating achieve a CO2 permeance of 2174 gas permeation units and CO2/N2 selectivity of 30 at -20 degrees C, highlighting their industrial relevance. This study establishes a scalable method for fabricating high-performance microporous polymeric membranes with exceptional stability for sustainable energy and environmental applications.